A Novel Extract of Fenugreek Husk (FenuSMART™) Alleviates Postmenopausal Symptoms and Helps to Establish the Hormonal Balance: A Randomized, Double‐Blind, Placebo‐Controlled Study. (13th July 2016) - Shamshad Begum, S.; Jayalakshmi, H. K.; Vidyavathi, H. G.; Gopakumar, G.; Abin, Issac; Balu, Maliakel; Geetha, K.; Suresha, S. V.; Vasundhara, M.; Krishnakumar, I. M.
Abstract : Despite the widespread use of hormone replacement therapy, various reports on its side effects have generated an increasing interest in the development of safe natural agents for the management of postmenopausal discomforts. The present randomized, double‐blinded, placebo‐controlled study investigated the effect of 90‐day supplementation of a standardized extract of fenugreek ( Trigonella foenum‐graecum ) (FenuSMART™), at a dose of 1000 mg/day, on plasma estrogens and postmenopausal discomforts. Eighty‐eight women having moderate to severe postmenopausal discomforts and poor quality of life (as evidenced from the scores of Greene Climacteric Scale, short form SF‐36® and structured medical interview) were randomized either to extract‐treated ( n = 44) or placebo ( n = 44) groups. There was a significant ( p < 0.01) increase in plasma estradiol (120%) and improvements on various postmenopausal discomforts and quality of life of the participants in the extract‐treated group, as compared with the baseline and placebo. While 32% of the subjects in the extract group reported no hot flashes after supplementation, the others had a reduction to one to two times per day from the baseline stages of three to five times a day. Further analysis of haematological and biochemical parameters revealed the safety of the extract and its plausible role in the management of lipid profile among menopausal women. Copyright © 2016 John Wiley & Sons, Ltd.